An exploration of possibilities for information and communications technologies in pursuit of enhanced public participation in lawmaking post Covid-19 - Cilliers, Ina (My University, 2022)
The purpose of this project was to explore the nature and impact of public participation practice in the legislative processes of the Gauteng Provincial Legislature (GPL) during and after the Covid -19 pandemic. The disruption to social interaction brought about by the Covid-19 pandemic had an impact on the design, implementation, and evaluation of public participation (PP) in the province. The scope and extent of this disruption was uncertain, yet rapidly evolving and scaling globally. For the GPL to fulfil its constitutional mandate and its commitments citizens, new opportunities for PP had to be explored and threats to PP had to be ameliorated in the context of a “new normal”. The research question is: “How can the information and communications technology revolution be leveraged to enhance public participation in legislative processes.” The study examined historic practice of the institution as well as virtual public hearings and portfolio committee business conducted during the Covid-19 pandemic in 2020 and 2021.The sample population for this study was public participation specialists and participants in the legislative sphere in Gauteng Province, South Africa. A purposive sample was drawn from the GPL community, specifically PP Unit staff, researchers and committee support staff. Focus group discussions were conducted with 18 participants. The public participation events observed included 3 public hearings, 3 sector parliaments, 2 round table events and 1 legislative workshop. The document analysis focused on reports that was tabled for the legislation under scrutiny in the relevant portfolio committees. The study identified threats and opportunities for PP, spaces of disruption and contestation that would require new areas of practice and new skills to be learnt by PP practitioners. The institutions’ journey from traditional PP practice to fully virtual and the resultant pivot to digital innovation was explored. Recommendations were structured around the design, implementation and evaluation of PP in the post-pandemic future. The paradigms of digital marketing and traditional PP practice was assimilated to suggest new ways of conducting the PP mandate that advance deliberation, inclusivity, and quality of lawmaking
A research report submitted in fulfilment of the requirements for the degree of Master of Management in Governance to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, 2022
Keywords: UCTD; Artificial Intelligence; Communications technologies; Lawmaking; Covid-19; SDG-11: Sustainable cities and communities